Nationwide Twin Birth Weight Percentiles by Gestational Age in Taiwan - I-Jan Hu; Chia-Jung Hsieh; Suh-Fang Jeng; Hui-Chen Wu; Chien-Yi Chen; Hung-Chieh Chou; Po-Nien Tsao; Shio-Jean Lin; Pau-Chung Chen; Wu-Shiun Hsieh (Elsevier, 2015)
Nationwide birth weight norms for twins have been reported in several countries across different ethnicities, but such data have not been established in Taiwan. The purpose of this study was to develop reference growth charts that are population-based and contain the information of birth weight percentiles by gestational age for twin neonates in Taiwan. Methods: In this study, we collected nationwide birth weight data for twins by sex and gestational age through the Taiwan Birth Registry. Percentiles, means, and standard deviations of birth weight for each 1-week increment of gestational age from 21 weeks of gestation were estimated and smoothed using weighted polynomial models. Results: The 10th, 50th, and 90th percentiles of birth weight born at the 37th gestational week were 2174 g, 2580 g, and 3125 g for male twins, respectively, and they were 2100 g, 2500 g, and 3000 g for female twins, respectively. The 10th, 50th, and 90th percentiles of birth weight born at the 40th gestational week were 2326, 3285, and 3790 g for male twins, respectively, and they were 2200 g, 2770 g, and 3690 g for female twins, respectively. Conclusion: This is the first nationwide birth weight norm for twins in Taiwan, which is particularly useful for investigation into the predictors and outcomes of altered fetal growth through twin studies in the Taiwanese population.